KEPEMIMPINAN ANIES BASWEDAN SEBAGAI GUBERNUR DKI JAKARTA - Alfroki Martha; Ade Yatma; Nadra Yanti; Resti Yuliana (STKIP Subang, 2023)
Anies Baswedan's leadership as Governor of DKI Jakarta has been in the spotlight since the beginning of his term of office. including the main policies implemented during his term of office, including placing community welfare as the main priority. Various programs have been launched to improve the quality of life of Jakarta residents, including in the fields of education, health and social services. Anies Baswedan's leadership also characterizes his commitment to infrastructure development. Large projects such as the construction of public transportation and revitalization of public spaces are the focus for increasing the comfort and mobility of Jakarta residents. Despite receiving criticism regarding several delays and obstacles, these efforts reflect a determination to improve the condition of the city's infrastructure. Overall, Anies Baswedan's leadership as Governor of DKI Jakarta shows various efforts to improve the welfare of the community and city infrastructure. This article will present an in-depth review of the various policies and projects that have been implemented during his tenure, as well as evaluating their impact on the citizens of Jakarta and Anies Baswedan's overall leadership image. This research was also conducted with the aim of discovering Anies Baswedan's leadership style when he served as Governor of DKI Jakarta, by applying descriptive qualitative research methods. The data sources in the research were obtained from primary data through literature studies in various reading.